2019
DOI: 10.1111/ecc.13076
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in long‐term survivors with localised prostate cancer by therapy—Results from a population‐based study

Abstract: Objective: Several therapies for localised prostate cancer (PC) are available; all yield similar survival rates. However, each therapy has significant side effects that can influence patients' health-related quality of life (HRQoL) in the long run. Methods:The study sample included 911 survivors with localised PC, 5-15 years post-diagnosis who were identified from the population-based CAESAR + study in Germany. HRQoL was assessed using the EORTC QLQ-C30 and EORTC QLQ-PR25 questionnaires. The association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 37 publications
(75 reference statements)
4
14
0
Order By: Relevance
“…Finally, patients who received ADT experienced greater burden over time. This is consistent with previous studies suggesting the diminished quality of life in patients who have been treated with ADT (12)(13)(14). What is surprising is that the self-reported burden in ADT cohort extended beyond the time frame in which testosterone recovery occurs (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, patients who received ADT experienced greater burden over time. This is consistent with previous studies suggesting the diminished quality of life in patients who have been treated with ADT (12)(13)(14). What is surprising is that the self-reported burden in ADT cohort extended beyond the time frame in which testosterone recovery occurs (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…Proportion of long-term bowel dysfunction as evaluated by the EPIC questionnaire was higher in the EBRT group [1], while no difference between subgroups was observed in our study. In the CAESAR+ study [31], patients treated with RP or EBRT reported better QoL than patients receiving combined treatments, while two other studies showed that global QoL did not significantly differ in the long-term, irrespective of treatment [29,32]. Two other studies have also looked at the long-term sequelae of the management of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, patient-reported treatment-related long-term AEs are more frequent and more severe in patients who in addition to RP have undergone post-RP RAD [5][6][7][8][9][10][11][12][13]. The impact of post-treatment changes of dysfunctions/problems since the pre-RP situation on HRQoL, assessed by validated patient-completed questionnaires is, however, relatively uncertain, and more research on this field is needed.…”
Section: Introductionmentioning
confidence: 99%